Praise and Wisdom in the Abbasid Poetry )Abu Tammam, a Model - Nazim, Muhammad Khalid (International Journal of Psychosocial Rehabilitation, 2020)
The research came in preparation and four chapters, and stood in preparation for the positions of ancient critics. The Abbasid era is the golden age but rather is the juices of the ages because of the breadth of knowledge in it, for the interest of the caliphs and the scholars of the cultures of other nations in all scientific and technical issues. The doctrine of progress has included literature, so his methods came as an example of the civilization of countries and their cultures and the way they taste the arts. It is because the arts deny the restrictions, which in their entirety are the reality of creativity. Who adds his contributions to the further deepening of thought, as the more the angles of reading increase the deeper the idea because it confirms understanding and documents spiritual, linguistic and moral value. In writing the humble and tagged research: I praise and wisdom in the Abbasid poetry (Abu Tammam, a model), and the deductive inductive approach.